ETHICAL ISSUES IN EPIDEMIOLOGICAL STUDIES - Kumar, Chirom Ranjeev; Shantaji, Thokchom; Gaidhane, Abhay (International Journal of Clinical and Biomedical Research, 2018)
Epidemiology is the study of the distribution and determinants of health related states and events in populations, and its application to the control of health problems. An epidemiological studies involve the population and as such ethical issues are an important aspect of it which need to be properly understood and adhered to. These issues can relate to informed consent, appropriate sample size, selection of participants, confidentiality, conflict of interest etc. Studies like therapeutic trial have also a lot of ethical issues which differ from issues pertaining to non-therapeutic trials. The source of funding for the study can have implication. Fabrication of data, manipulation during analysis, intentional changes in the result to obtain a pre desired outcome are some grey areas which need to be addressed. Another ethical issue is publication in certain Journals with monetary involvement. Lastly but not the least, authorship also have certain ethical issues. Attention to ethical issues can facilitate the effective planning, implementation, and growth of a variety of public health programs and research activities. Moreover with advancement in Epidemiology like molecular epidemiology, genetic epidemiology etc. the ethical issues become more complicated. Keywords: Ethics; Epidemiology; Epidemiological studies; Ethical Issues.